# I had asked that how: (-)(-)= (+). I saw that in that, (-) (+) = (-)... Prove how(-) (+) = (-). I am asking this again. Sorry for the impatience. I know experts have to see quite a many questions globally, so there may be some time taken to answer the questions.. So, just see to this a little soon.

Dear student

Regards

• -2
If there are different signs they subtract and when there signs are same then they add..let's see an example=1. (-3+3)=0(because there signs are different)2. (-3-3)=6(because there signs are same) Hope it helps....and also please help my channel to grow by subscribing it....my channel name is 'Sticky paperqueen'...if you like my videos give a thumbs up...
• 0
example -11+5 = -6
• -1
example -11+5 =-6
• -1
It is a fact that (-) (+) = (-)
for example  -13+2= -11
• -1
Actually its the law of integer as we have studied in our school .It is the basic concept in which <-> <-> =<+> so its not the complicated case that you have asked ..sorry for unrespect but don't mind

-Satvik Phour

• -1
You all are just telling or repeating the same law... But it is definitely not a formal proof. You just repeated the same rule by just taking the example. But can you say how this happened : (-)(+)=(-)? You know when I had asked (-)(-)=(+)..The expert( Brijendra Pal sir) gave me very accurate formal proof using just distributive law or property.. So please be specific...
• 0
What are you looking for?